ANALISIS YURIDIS PELANGGARAN HUKUM PADA INVASI RUSIA-UKRAINA DITIJAU DARI KONVENSI JENEWA 1949: JURIDICAL ANALYSIS OF LEGAL VIOLATIONS IN THE RUSSIA-UKRAINE INVASION, VIEWED FROM THE GENEVA CONVENTIONS OF 1949 - Rizqiah, Siti Nur; Rachmadyantira, Kyla; Maharani, Adellia Puan; Angkasari, Wildani (Fakultas Hukum Universitas Trisakti, 2024)
The invasion of Russia into Ukraine is an unforeseen condition that can disrupt world stability and peace. This war occurred due to the invasion of Russian military forces into Ukraine, as Ukraine joined NATO, which was perceived as a threat to Russia's security. Consequently, there have been violations of international humanitarian law as regulated in the Geneva Conventions. The objective of this research is to analyze legal violations in the Russia-Ukraine invasion from the perspective of the Geneva Conventions of 1949. The research method employed is juridical-normative research with a statute approach and case approach, using legal material tracing the perspective of the Geneva Conventions of 1949. The research method employed is juridical-normative research with a statute approach and case approach, using legal material tracing through library research for descriptive analysis. The results of this research show a juridical analysis of legal violations in the Russia-Ukraine invasion, viewed from the Geneva Conventions of 1949, indicating a series of actions that violate norms of international humanitarian law, regulated in the Geneva Conventions IV and II. These actions resulted in casualties, both injuries and fatalities, among civilians who should have been protected from invasion. Additionally, attacks on infrastructure, including energy and educational facilities, violate the principles of the Geneva Conventions that prohibit disproportionate destruction for military objectives and impact international trade activities. The responses from other countries to the Russia-Ukraine invasion include condemnation from various nations, including the European Union and Indonesia, regarding the violations of international humanitarian law. Therefore, accountability is deemed necessary.